Social engagement: Hearing the experiences of disabled students in higher education in Ireland - Rath, Vivian (Frontiers in Education, 2022)
Research on the experiences of disabled students in higher education in Ireland has focused primarily on barriers to their transition and academic experiences post entry. Their wider social engagement experiences have yet to be explored. Early and ongoing social engagement has been found to be particularly beneficial for non-traditional students leading to the creation of sense of belonging and greater student retention. There has been limited consideration of this area within Irish policy or research. As a disabled researcher with a human rights perspective. I adopted a qualitative framework which combined the transformative paradigm with the bio-ecological model. This approach enabled me to place the voice of the student at the centre of the research whilst examining the system around them. The research upon which this article draws upon the findings of research carried out by a disabled researcher which brought together data from 65 participants, with representatives from 19 Higher Education Institutions (HEIs) across the Republic of Ireland using a four-phased, sequential, and concurrent qualitative data collection methodology (Rath, 2020b). This paper focuses on the disabled undergraduate student cohort from this research (n = 23) and the theme of social engagement. The key findings under the theme of social engagement included, (i) Social engagement was highly valued and recognised as being vital to the formation of connections that resulted in a sense of belonging. (ii) The majority of disabled students reported being socially engaged, yet almost all reported barriers to their social engagement. (iii) A lack of disability awareness, inaccessible physical infrastructure, peer and staff attitudes, negatively impact upon students’ sense of value, ability to maintain friendships and develop a sense of belonging. (iv) There was little evidence of structures or a strategic approach to disabled students’ social engagement. These findings resonate with international research which demonstrated that disabled students face a range of systemic barriers to their social engagement in higher education. The implications of this research point to a failure of national and institutional policy to adequately consider the social engagement opportunities of disabled students within higher education.